Community Contribution to the Development of Community-Based Drinking Water and Sanitation Provision (Pamsimas) in Rappolemba Village, Tompobulu District, Gowa Regency - Muh. Anwar (Journal Of Social Science (JoSS), 2026)
This study investigates the role of community contributions in the development and sustainability of the Community-Based Drinking Water and Sanitation Provision (Pamsimas) in Rappolemba Village, Tompobulu District, Gowa Regency. The PAMSIMAS program is a government initiative aimed at improving access to clean water and sanitation through community empowerment. The research explores how local participation influences the planning, implementation, and maintenance phases of the program. Using a qualitative research method, the study involved interviews and field observations to gather insights into the community’s active role. The findings reveal that community contributions are crucial at all stages, from participatory planning deliberations to mutual cooperation during infrastructure development and routine maintenance activities. Despite these contributions, challenges such as low collective awareness, financial constraints, and community members’ busy schedules hinder full participation. The study emphasizes the need for greater public awareness and financial commitment to ensure the long-term sustainability of PAMSIMAS facilities. The results underline the importance of fostering a sense of ownership and responsibility among community members to achieve sustainable development outcomes. Ultimately, the study provides strategic recommendations for enhancing community involvement and addressing obstacles to strengthen the sustainability of PAMSIMAS in rural settings.